Exploration and practice of piano teaching reform in local colleges and universities - LIN, JING (Pacific International Journal, 2024)
Piano is the most used and most important teaching aid in preschool education practice, and piano assisted teaching is also the most popular form of preschool education. So, training pre-school teachers with professional piano playing skills and comprehensive music knowledge is the most important problem facing pre-school piano teaching. How to carry out piano teaching practice in combination with college teaching and comprehensively improve the piano playing skills of preschool education students has become a very realistic problem faced by preschool education majors in colleges and universities. As a piano teacher in a university, on the basis of combining piano teaching practice, the author uses literature method and investigation method to investigate the current situation of piano teaching in preschool education major of Linyi University from the perspective of social needs and professional development, makes an objective analysis of the teaching situation, finds problems and puts forward countermeasures. Through exploration and practice, the author thinks that we should attach importance to students' piano foundation and improve students' motivation to learn piano. Teachers should strengthen the rational use of teaching methods and pay attention to the guidance of students' learning methods; In the reform of teaching organization form, group class should be the main, supplemented by individual teaching; Strengthen teaching feedback; Attach importance to the improvement and development of teachers' profession, and find a new way suitable for the piano teaching of preschool education in local colleges and universities, so as to send a group of qualified preschool teachers to the society.